"Something fruitful for all of us": Social annotation as a signature pedagogy for literature education. (July 2021) - Clapp, Jeffrey; DeCoursey, Matthew; Lee, Sze Wah Sarah; Li, Kris
New social annotation practices have the potential to become a "signature pedagogy" for educators in literary studies, because social annotation encapsulates both the expected learning outcomes and the underlying value commitments of literature education. We give an account of a project conducted by colleagues at the Education University of Hong Kong, during which colleagues explored social annotation technologies in literary studies courses. After implementing social annotation in our courses, instructors held roundtable discussions, collected surveys and conducted focus group interviews. Basing our interpretation of these data on Louise Rosenblatt's transactional theory of reading and writing, we propose that social annotation can help students engage with literary texts more effectively by showing them how to move toward an aesthetic mode of reading. Students participating in social annotation, moreover, understood its application to literary studies in ways that directly reproduced Rosenblatt's account of literary interpretation.